Defiant requiem - Neuwirth, Bebe; Shultz, Doug; Schnall, Peter; Partisan Pictures; Public Broadcasting Service (U.S.); Defiant Requiem Foundation; PBS Distribution (Firm) ([United States] : PBS Distribution, 2013)
In the face of horrific living conditions, Jewish inmates of Terezin concentration camp-artist, musicians, poets and writers-fought back with art and music. Led by conductor Rafael Schachter, they re-imagined a Catholic liturgical work, Verdi's Requiem, as a condemnation of the Nazis. They performed for Nazi brass, singing what they dared not say. Six decades later, a new conductor and choir take Verdi's Requiem back to Terezin to bring the story of Schachter's artistic uprising back to life.
Documentary.
Title from container.
Narrated by Bebe Neuwirth.
Rating: TV-PG.
DVD, region 1 ; 5.1 surround.
Subtitled for the deaf and hard of hearing.
Keywords: Schacter, Rafael; Theresienstadt (Concentration camp); Prisoners of war as musicians; Prisoners of war as artists; World War, 1939-1945 -- Prisoners and prisons; Documentary films; Films for the hearing impaired; Video (DVD); Historical films